Kajian Nilai Sosio Religius Pada Upacara Nyakap Uma Di Subak Umalas Desa Canggu Kecamatan Kuta Utara Kabupaten Badung - Ni Wayan Murniti; Putu Sri Marselinawati (Jayapangus Press, 2023)
Land conversion in tourism areas such as Canggu Village has an impact on soil fertility. The subak system, which always involves a ceremony in every agricultural activity, often carries out the nyakap uma ceremony. The nyakap uma ceremony is a ceremony to ask Dewi Sri to live on agricultural land so that everything that is planted can grow well. The purpose of this study was to determine the socio-religious values ​​contained in the nyakap uma ceremony, religiously the nyakap uma ceremony is based on Hindu literature and socially the nyakap uma ceremony prioritizes mutual cooperation involving social interaction. This type of research is a qualitative research with a phenomenological approach. The primary data sources in this study were interviews with members of the Umalas subak, Canggu Village, Badung Regency, and secondary data sources in this study were research results and books related to agricultural activities. Data collection techniques in this study were observation, interviews, and literature study. The stages of the Nyakap uma ceremony procession in Subak Umalas Canggu Village are the stage of preparing the ceremony facilities and infrastructure, the place and time of the Nyakap uma ceremony, and the day before the ceremony, the land owner circles his farm with a piglet that will be used as a suckling pig during the ceremony. The function of the nyakap uma ceremony is a religious function, a function of social interaction, a function of fertility, and a function of nature conservation. Socio-religious values ​​in the implementation of the nyakap uma ceremony, namely, divine values, namely the nyakap uma ceremony as an expression of gratitude to God, social values, namely the nyakap uma ceremony as social media between communities in Canggu village, and aesthetic values, namely the value of beauty or art in ceremonies say umma. From the results of the study it can be concluded that the nyakap uma ceremony contains socio-religious values ​​as seen from its religious values and social interaction.